Positive Rate of Noninvasive Prenatal Screening for Pregnancies with Fetal Congenital Heart Disease and Its Impact on Pregnancy Outcome - Yun Chen; Yun-Li Lai; Yi-Ping Shen; Xiao-Xian Tian; Chen-Guang Zheng; Hong-Wei Wei; Yang Pan; Dan-Dan Shi (Wolters Kluwer Health, 2020)
Abstract. Objective:. To evaluate the clinical utility of noninvasive prenatal screening (NIPS) for fetuses with congenital heart disease (CHD) and impact of NIPS results on pregnancy outcome. Methods:. This was a retrospective study of pregnant women with fetuses diagnosed with CHDs by sonographic examination, who willing to underwent NIPS as a side-test for fetal aneuploidies. From August 2016 to October 2017, in the sonographic examination center of Maternal and Child Health Hospital of Guangxi Zhuang Autonomous Region. NIPS was offered to 117 women who carried fetuses with CHD diagnosed by fetal ultrasound (mean gestational age = 24 weeks). The pregnancy outcomes were followed-up. Results:. NIPS positive rate in our pregnancies with CHD fetuses' cohort is 11.1% (13/117), and the positive predictive value for aneuploidies is 85.7% (6/7). In the NIPS positive group (n = 13), all pregnancies terminated, 76.9% (10/13) of those decisions were made on ultrasound finding alone. In the NIPS negative group (n = 104), 2 lost follow-up, 79 pregnancies terminated, among which 77.2% (61/79) of the decision was made by ultrasound results alone. Twenty-three pregnancies continued and 78.3% of those fetuses carried single type CHD. In terminated pregnancies that did not considered NIPS results (71/115), 73.2% (52/71) of those carried fetuses with two or more types of CHDs. Conclusion:. NIPS can detect common aneuploidy associated with CHD with high positive predictive value and screening yield. The NIPS result played certain meaningful roles in determining pregnancy outcomes, particularly for fetus with simplex CHD; yet the parents' decision of pregnancy was mainly made based on ultrasound findings.